Text, Context and Natural Conservation: An Analysis of Muhammadiyah’s and Nahdlatul Ulama’s Islamic Legal Thought on Fiqh of Environment - A. Alamri, Mohammed Saeed; JM Muslimin; K. Wsuwetsa Mukti; Rayhansyah Jasin (Nurani, 2025)
This study seeks to examine the dynamics of Islamic legal reasoning applied by Muhammadiyah and Nahdlatul Ulama (NU) in addressing environmental challenges, with particular attention to the paradox reflected in their acceptance of mining concessions granted by the state. In Indonesia, Muhammadiyah and NU have long played significant roles in environmental discourse through fatwas, congress resolutions, and official statements that emphasize ecological responsibility. However, their recent acceptance of mining concessions raises critical questions regarding moral consistency and the direction of Islamic legal reasoning. This research employs a socio-legal approach by examining official documents issued by both organizations using the combined framework of uṣūl al-fiqh and socio-legal theory. The analysis focuses on patterns of legal reasoning, sources of legitimacy, and the socio-political dynamics shaping institutional ijtihād. The findings indicate that Muhammadiyah predominantly applies a purificatory, normative textual, rational, and systematically organized approach, while Nahdlatul Ulama (NU) demonstrates a more flexible and contextual orientation that is deeply rooted in classical fiqh traditions. Nevertheless, in the context of mining concessions, both organizations exhibit a shift toward pragmatic-economic interpretations of religious texts and maqāṣid al-sharī‘ah. This shift exposes a fundamental tension between normative ideals and political–economic realities, highlighting the susceptibility of Islamic legal reasoning to structural pressures. This article contributes to the advancement of fiqh al-bi’ah within Indonesian Islamic legal scholarship by providing a critical reflection on the future direction of Islamic jurisprudence that maintains a strong commitment to ecological justice while engaging the complexities of contemporary socio-political realities.